Inovasi Inovasi Pendidikan Moderasi Keagamaan Di SMA Muhammadiyah 2 Surabaya - Bina Prima Panggayuh; Akh Muzakki; Hanun Asrohah; Akh. Syaiful Rijal (TADRIS: Jurnal Pendidikan Islam, 2022)
This study aims to find out the process and implications of the educational process of religious moderation, so that it can be used as an evaluation and as a basis for better education. The research method used in this research is qualitative and with a descriptive analytic approach. The results of this study show that innovation in religious moderation education is found in the principal's policies, curriculum, habituation programs, and activities outside of learning such as extracurricular activities, commemoration of Islamic holidays, and other religious activities by mainstreaming the principles of religious moderation, namely tawassuth, ta'adul, and tawazun.